Give me your hand - Abbott, Megan., 1971- (Little Brown and Company, 2018)
Kit Owens harbored only modest ambitions for herself when the mysterious Diane Fleming appeared in her high school chemistry class. But Diane's academic brilliance lit a fire in Kit, and the two developed an unlikely friendship... until Diane shared a secret that changed everything between them. More than a decade later, Kit thinks she's put Diane behind her forever, and she's begun to fulfill the scientific dreams Diane awakened in her. But the past comes roaring back when she discovers that Diane is her competition for a position both women covet: taking part in groundbreaking new research led by their idol. Soon enough, the two former friends find themselves locked in a dangerous grame of cat-and-mouse that treatens to destroy them.